A influência da escolaridade na renda dos trabalhadores amazonenses: uma análise para os anos de 2013 a 2019 - Costa, Diogo Pacheco (Brasil, 2025)
This study aims to analyze the impact of educational attainment on the income of workers in the state of Amazonas between 2013 and 2019. The primary objective is to understand how education influences earnings in the region, identifying the state of the art on the relationship between economic development and education, defining the concept of human capital, and examining how educational attainment affects the income of workers in Amazonas. This topic is justified by the relevance of education as a strategic factor for economic and social development. It is a descriptive documentary study employing qualitative and quantitative methods for data analysis. The research relies on secondary and primary sources, including the Continuous PNAD (IBGE), RAIS, and relevant academic literature. The results show that higher levels of education are directly associated with higher earnings and fewer working hours, reflecting more favorable working conditions and highlighting education as an essential tool for social mobility and the promotion of a fairer and more equitable labor market.